ANALISIS STRATEGI PENGEMBANGAN SISTEM PELAYANAN JARINGAN AIR BERSIH PERPIPAAN DI KELURAHAN BULUROKENG KECAMATAN BIRINGKANAYA KOTA MAKASSAR - Latief, Rudi (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2019)
In the research the author did this about the strategy of developing piped clean water systems in Bulurokeng Village, Biringkanaya District, Makassar City. In serving and distributing clean water needs to customers, the demand for conformity of clean water to the standards set is important and must be considered in meeting the needs of clean water for the community. However, the piped water network service system that occurs in the Bulurokeng Sub-District of Makassar City is very low because it is seen from the community's failure in meeting clean water needs.Rupyanti Sinaga dan Rahmawati, 2013. This study uses a variable of Water Requirement, Topographic Location of service area, and Type of system connection, The analytical approach used in this study is the Quantitative Approach. In this study using the SWOT Analysis Tool, To Answer the Formulation of the Problem Problem Development Strategy Improving the service of the piped water network system in the Makassar Bulurokeng Subdistrict.Based on the SWOT Analysis conducted, the conclusions in this study are the direction of the development strategy for improving the service of the clean water network system in the Bulurokeng Subdistrict, namely the SO Strategy.